Arcadia Falls - Goodman, Carol (New York : Random House Large Print, 2010)
After losing her husband Meg Rosenthal and her daughter Sally move to Arcadia Falls where she takes position teaching at a boarding school. During the First Night bonfire one of her student's plunges to her death in a campus gorge. Meg is unnerved by the sheriffs interest in the girl's death and as long-buried secrets emerge, she must face down her own demons and the danger threatening to envelop Sally.
edited hb 2015-06-16
Keywords: Life change events -- Fiction; Mothers and daughters -- Fiction; Detective and mystery stories